Severe pediatric adenoviral pneumonia combined with invasive pulmonary aspergillosis - Shuihua Huang; Shengxin Zhang; Lin Yuan; Zhiqiang Zhuo; Xingdong Wu (BMC Pulmonary Medicine, 2023)
Abstract Background This study aimed to analyze the clinical characteristics of severe pediatric adenoviral pneumonia combined with invasive pulmonary aspergillosis. Methods We retrospectively analyzed the clinical data of five children clinically diagnosed with severe adenoviral pneumonia combined with invasive pulmonary aspergillosis at Xiamen Children’s Hospital. Results These five children included one boy and four girls, with ages of onset ranging from 8 months and 15 days to 2 years and 2 months. All of them had fever with a mean duration of 11–35 days and cough. Pulmonary imaging was performed, which revealed solid pulmonary opacification in all five children, pleural effusion in two children, and emphysema and multiple small cavity formations in one child. Multiple microbiological tests were performed on the 5 children, and adenovirus was positive in the alveolar lavage fluid for the first time, and aspergillus culture was positive in the second test. On tracheoscopy, the bronchial mucosa was seen to be congested and edematous or pale and eroded; white moss-like material was seen adhering to the tracheal wall or even blocking the airway. The five children were treated with a combination of two or more broad-spectrum antimicrobials, glucocorticoids, and gamma globulins and underwent bronchoscopy. Voriconazole was added in the treatment regimen after the diagnosis of aspergillosis (28–34 days of treatment). Four of the children were discharged in good condition with a mean total length of hospital stay of 17–47 days. The other child leave against medical advice. Follow-up 3–5 months after discharge showed that one child had been cured; two children had developed obliterative bronchiolitis; one child had developed bronchiectasis; and the remaining child who had been discharged spontaneously was not contactable via telephone. Conclusions Immune disorders and antibiotic and steroid treatments for adenovirus infection are high-risk factors for secondary invasive pulmonary aspergillosis in children. Prolonged fever and cough are the main manifestations, but which lack specificity, and bronchoscopic mucosal-specific injury evaluation and alveolar lavage fluid culture are helpful in the diagnosis of aspergillosis. The long-term prognosis of severe pediatric adenoviral pneumonia combined with invasive pulmonary aspergillosis maybe poor.